The reception of Vatican II - Lamb, Matthew L.; Levering, Matthew (Oxford University Press, 2017)
The Constitutions -- Sacrosanctum Concilium (the sacred liturgy) / Jeremy Driscoll, O.S.B -- Lumen Gentium (the Church) / Guy Mansini, O.S.B -- Dei Verbum (Divine Revelation) / William M. Wright IV -- Gaudium et Spes (the Church in the modern world) / Thomas Joseph White, O.P -- The decrees -- Christus Dominus (the pastoral office of the Bishops in the Church) / Matthew Levering -- Presbyterorum Ordinis (the ministry and life of priests) / David Vincent Meconi, S.J -- Optatam Totius (the training of priests) / Bishop Robert Barron -- Perfectae Caritatis (the up-to-date renewal of religious life) / Sara Butler, M.S.B.T -- Apostolicam Actuositatem (the apostolate of lay people) / Michele M. Schumacher -- Ad Gentes (the Church's missionary life) / Ralph Martin -- Unitatis Redintegratio (ecumenism) / Matthew J. Ramage -- Orientalium Ecclesiarum (the Eastern Catholic Churches) / Adam A. J. DeVille -- Inter Mirifica (the means of social communication) / Daniella Zsupan-Jerome -- The declarations -- Dignitatis Humanae (freedom of religion) / Nicholas J. Healy, Jr -- Gravissimum Educationis (Christian education) / Paige E. Hochschild -- Nostra Aetate (the relations of the church to non-Christian religions) / Gavin D 'Costa